Effect of arsenic trioxide along with tannic acid, di-sodium hydrogen phosphate, alum and effects of sand-charcoal-iron-filter bed filtrated water along with alum on body weight and some hematological parameters in rabbit - Ahmed, Shaifuddin; Siddiqui, Md Saiful Islam; Islam, Kamrul; Gani, Mohammad Usman; Moonmoon, Sharifunnessa; Rashid, Md Harun Or; Awal, Md Abdul (Asian Journal of Medical and Biological Research, 2016)
<!–[if gte mso 9]> ismail - [2010] 11.5606 <![endif]–> The effect of arsenic trioxide along with tannic acid, di-sodium hydrogen phosphate (DSHP), alum and effects of sand-charcoal-iron-filter (SCIF)-bed filtrated water along with alum on body weight and some hematological parameters were carried out on a total of 30 (01 month old) adult Newzealand white rabbits. The Rabbits were randomly divided in to 6 equal groups (A,B,C,D,E & F) at the ratio of three males and two females in each group, rats of group A was kept as control without giving any treatment, rabbits of group B received arsenic trioxide@100 ppm, group C received arsenic trioxide @ 100 ppm plus tannic acid @100 ppm, group D received arsenic trioxide @ 100 ppm plus di-sodium hydrogen phosphate @100 ppm, group E received arsenic trioxide @100 ppm plus alum @100 ppm orally daily for 60 days in all cases and group F received alum @100 ppm in SCIF-bed filtrated water orally daily for 60 days. The result showed that body weight gain of control group (A) per week per rabbit was found to increase but in treated group B (arsenic trioxide@100ppm orally daily) the mean body weight of group B were decreased gradually and significant (P<0.05) decrease in body weight was observed at 40 days of feeding and at day 60 it was highly significant (P<0.01). Rabbits of group C, D and E were apparently normal and mild body weight reductions were observed which was statistically insignificant. No body weight loss was observed in rabbit of group F. TEC, Hb and PCV were slightly reduced in group C, D, E and F but highly significant (P< 0.01) reduction of TEC, Hb and PCV were observed in group B. ESR values were slightly increased in group C, D, E and F but highly significant (P< 0.01) increased of ESR value was observed in group B. Leukocytosis was observed in rabbits of group B. In this study, it was concluded that treatment with arsenic oxide at low doses has harmful effects on experimental animals including hematological alterations. Asian J. Med. Biol. Res. March 2016, 2(1): 38-47 <!–[if gte mso 9]> Normal 0 false false false MicrosoftInternetExplorer4 <![endif]–><!–[if gte mso 9]> <![endif]–><!–[if gte mso 10]> <![endif]–>